Pengelolaan sampah di Tembokrejo Kota Pasuruan: Penggunaan Biopori dan Incinerator Domestik - Abdul Aziz; Amirotul Muniroh; Qurrotul A’yuni; Mila Sunarti; Laila Rahmadayanti Putri (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
Making environmentally friendly biopores and domestic incinerators is one method of waste management that can be used to overcome waste problems, both organic and non-organic waste management. This article discusses innovations in waste management in Tembokrejo, Pasuruan City through the use of environmentally friendly Biopores and Domestic Incinerators to overcome the waste problem in the subdistrict of Tembokrejo. Waste is one of the problems that until now has not been resolved properly. So an effective waste management strategy is needed to avoid environmental pollution. The use of biopores and environmentally friendly domestic incinerators is one of the waste management techniques. By using organic waste for biopores and an environmentally friendly Domestic Incinerator for burning non-organic waste with minimal smoke so it doesn't pollute the environment. . The method used in this service activity consists of four stages, namely Observation, Preparation, Implementation, Evaluation. The result of this service is a change in people's attitudes and behavior towards waste management through the innovation of using Biopores and Domestic Incinerators so that they are starting to be interested in using this innovation to make the sub-district of Batasrejo free from the difficulties of waste management.